(untitled) (Journal of Philosophy Culture and Political Science, 2018)
As is known, Eurocentrism (Europeanism) is a theoretical setting of modern concepts of social and political development, which emphasizes the leading role of Europe in world development, turns the values of European culture into the criterion of identification and reference system for research of other cultures, the European model of development into a universal way of solving all the complex problems of mankind. According to the Eurocentric point of view, Europe with its inherent spiritual way of life is the center of world culture and civilization. Exaltation of the West can be traced in the European consciousness over the centuries. Key words: Eurocentrism, Eurasian Union, culture, art, philosophy, ideology, power.